2019
DOI: 10.1002/pan3.8
|View full text |Cite
|
Sign up to set email alerts
|

An ecological theory of changing human population dynamics

Abstract: The dependence of humans on nature has come into focus as the human population continues to grow, resources diminish and production technology stagnates – threatening human well‐being on a global scale. Numerous previous models describe human population dynamics, in relation to a multitude of different factors. However, there are no consistent driving factors of human demography through history, which makes predicting future changes more challenging. Here, we review the literature on human population growth fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 67 publications
0
20
0
2
Order By: Relevance
“…This is supported by empirical data showing that there are two groups of individuals with distinct demography, development structures, and consumption patterns (Oswald et al, 2020), in addition to an analysis of The World Bank (2019a) data given in the appendix. We use this idea of distinct economies with distinct practices and apply it to an ODE model of global land management and population growth (Henderson and Loreau, 2019). We modified the Henderson and Loreau model to incorporate two regions, movement of people and goods and inequality.…”
Section: Brief Model Descriptionmentioning
confidence: 99%
“…This is supported by empirical data showing that there are two groups of individuals with distinct demography, development structures, and consumption patterns (Oswald et al, 2020), in addition to an analysis of The World Bank (2019a) data given in the appendix. We use this idea of distinct economies with distinct practices and apply it to an ODE model of global land management and population growth (Henderson and Loreau, 2019). We modified the Henderson and Loreau model to incorporate two regions, movement of people and goods and inequality.…”
Section: Brief Model Descriptionmentioning
confidence: 99%
“…Considering the exponential population growth on the planet [144], the request for greater food and consequently the need for an agricultural drainage evolution should be considered [145].…”
Section: Present Times (From 1900 To Today)mentioning
confidence: 99%
“…Agricultural land is exhausted and degraded, at different rates depending on the surrounding landscape, and ultimately becomes unproductive (Henderson and Loreau, 2019; Cramer et al, 2008). Natural land contributes to the recovery of surrounding land, acting, for example, as a species pool necessary for recolonization by native species (Cramer et al, 2008; Baeten et al, 2010).…”
Section: Model Descriptionmentioning
confidence: 99%
“…One study suggested that social inequalities and environmental degradation were present in all known past societal collapses (Motesharrei et al, 2014) and as such the authors proposed a general model showing various projections of socio-ecological collapses as a result of the feedbacks between social inequality and resource exploitation. More recently, Henderson and Loreau (2018) and Henderson and Loreau (2019) proposed a general theoretical framework to explain human demography across history in relation to resource accessibility, which can be used to explain the population explosion in the last century and potential future scenarios. Through an economic-ecological model Lafuite and Loreau (2017), Lafuite et al (2017) and Lafuite et al (2018) investigated how time lags in the response of biodiversity to anthropic perturbations can feedback on the human population via shortages in food production and undermine the sustainability of the socio-ecological system.…”
Section: Introductionmentioning
confidence: 99%